Lives “on hold” - Priscilla Boshoff (Communicare)
The relationship between a personal identity and the state-issued Identity Document (ID) is the focus of this article, which examines stories published in the “Horror Affairs” column of the popular South African tabloid, the Daily Sun. These highly emotional stories tell of the despair and desperation felt by individuals at the lack of an ID book, which is blamed on the inefficiency of the state Department of Home Affairs. In order to explicate this relationship I make use of Agamben’s notion of “bare life” and the camp in conjunction with Lacan’s idea of the Symbolic Order to argue that if the Identity Document provides the means by which the individual is made to signify, the lack of an Identity Document threatens to reduce the individual to “bare life”. By publishing the stories of those deprived of the visibility that the ID provides, the Daily Sun, I show, directly engages in this exchange, and, in contrast to Home Affairs, bestows its own even stronger gift of identity by the fact of appearance in its pages.